Mimicry of canonical translation elongation underlies alanine tail synthesis in RQC - Filbeck, Sebastian; Cerullo, Federico; Paternoga, Helge; Tsaprailis, George; Joazeiro, Claudio A. P.; Pfeffer, Stefan (Molecular cell, 2021)
Aborted translation produces large ribosomal subunits obstructed with tRNA-linked nascent chains, which are substrates of ribosome-associated quality control (RQC). Bacterial RqcH, a widely conserved RQC factor, senses the obstruction and recruits tRNAAla(UGC) to modify nascent-chain C termini with a polyalanine degron. However, how RqcH and its eukaryotic homologs (Rqc2 and NEMF), despite their relatively simple architecture, synthesize such C-terminal tails in the absence of a small ribosomal subunit and mRNA has remained unknown. Here, we present cryoelectron microscopy (cryo-EM) structures of Bacillus subtilis RQC complexes representing different Ala tail synthesis steps. The structures explain how tRNAAla is selected via anticodon reading during recruitment to the A-site and uncover striking hinge-like movements in RqcH leading tRNAAla into a hybrid A/P-state associated with peptidyl-transfer. Finally, we provide structural, biochemical, and molecular genetic evidence identifying the Hsp15 homolog (encoded by rqcP) as a novel RQC component that completes the cycle by stabilizing the P-site tRNA conformation. Ala tailing thus follows mechanistic principles surprisingly similar to canonical translation elongation.
Online veröffentlicht am 30. November 2020, Artikelversion vom 7. Januar 2021
Gesehen am 21.05.2021